Stimulation of dopamine receptors (type 2) lowers human intraocular pressure. Issue 12 (December 1985) - Mekki, Q A; Turner, P
Abstract : The interaction between bromocriptine and metoclopramide on intraocular pressure (IOP), pupil diameter, and other parameters were studied in healthy volunteers. Pupil diameter was not affected by both treatments and only bromocriptine lowered IOP. Prior treatment with metoclopramide blocked the IOP-lowering effect of bromocriptine. It is concluded that bromocriptine lowers IOP by stimulation of dopamine-2 receptors.